The impact of micro-banking offices on loan accessibility empirical evidence in the Philippines - David, Maria Khlya Lancelot C.; Pilapil, Agatha C.; Esguerra, Emmanuel F. (Quezon City School of Economics, University of the Philippines Diliman, 2019)
Developing countries such as the Philippines have always aimed for sustainable development. A major aspect of this kind of development is poverty reduction and inclusion for all, a pro_poor growth. Bangko Sentral ng Pilipinas has already specified targets, one of which is the implementation of BSP Policy No.694, _Amendment of Regulations on the Establishment of Other Banking Offices and Notes to Microfinance._ The policy includes a provision where the micro_banking offices are allowed to disburse or release micro_loans, and collect loan payment and other charges. The objective is to cause household borrowers to shift from informal loan sources to formal loan sources, specifically to microfinance institutions. This paper evaluates whether the observed shift to formal loan sources between 2008 and 2014 can be attributed to the said policy. Using a multinomial probit regression, the researchers examine different socio_economic variables that could possibly affect the household head_s decision on loan source availment. Sex, total income, work type, insurance, and grants are among these. Micro_Banking Office (MBO) density per municipality is used as the policy indicator to determine if the BSP_s policy action, which took place in 2010, can explain the observed outcome in 2014. Findings show that the presence of MBOs decreases the probability of a household availing from informal sources (family and friends, informal lenders). This supports the view that the significant shift of loan availment source, informal to formal, can be attributed to the said policy. This indicates the effectiveness of BSP policy on establishment of MBOs, improving then the financial inclusion in the country.
Thesis (B.S. Economics) -- University of the Philippines Diliman
Keywords: Microfinance -- Philippines; Micro-Banking Office (MBO).